Using art for public engagement: reflections on the Dementia and Imagination project. Issue 3 (1st September 2020) - Tischler, Victoria; Howson-Griffiths, Teri; Jones, Catrin Hedd; Windle, Gill
ABSTRACT: Creative outputs engage the public and can be used to share research. This paper reports on public engagement activities that were part of the research project Dementia and Imagination (D&I). We found that artwork and creative activities effectively engaged a range of audiences and challenged negative ideas about dementia. For the project team, public engagement developed relationships with collaborators and connected the research to different community settings, influencing future programmes of work. Further work could explore public engagement in diverse settings to assess which approaches are effective in maximising research value and wider community benefit.